A lithium battery separator and preparation method thereof

By coating polymer nanofiber hybrid coating on the surface of the lithium battery separator, the problems of separator temperature resistance and electrolyte wetting are solved, and the development of high-performance lithium battery separator is realized.

CN118448808BActive Publication Date: 2025-02-25ANHUI HUITONG NEW ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410697288.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-02-25
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

The lithium battery separator has problems of poor temperature resistance and electrolyte wetting, which affects the electrochemical performance and safety performance of the battery.

Method used

The polymer nanofiber coating is coated on the surface of the lithium battery separator by hybrid dispersion, including mixed modification of polyphenylene sulfide, polyacrylonitrile and polylactic acid nanofibers.

Benefits of technology

The temperature resistance of the diaphragm, the high wettability of the electrolyte and the high ionic conductivity are improved, and the electrochemical performance and safety performance are optimized.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a lithium battery separator and a preparation method thereof, and belongs to the technical field of lithium battery separators. In the invention, a polyolefin separator is used as a substrate, and a mixed slurry of polyphenylene sulfide, polyacrylonitrile and polylactic acid nanofibers is coated on the upper and lower surfaces of the separator to form a temperature-resistant coating. Based on the excellent temperature resistance of polyphenylene sulfide nanofibers, polyacrylonitrile and polylactic acid nanofibers are added for mixed modification to give the separator excellent electrochemical properties and hydrophilicity, thereby improving the temperature resistance and electrolyte wetting properties of the polyolefin separator. The polyacrylonitrile nanofibers enable the lithium battery separator to have a higher ionic conductivity, and the polylactic acid nanofibers have a hydrophilic group, which can improve the electrolyte wetting properties of the separator. The polymer nanofiber slurry prepared by the dispersion and mixing of the three improves the wettability, thereby obtaining a lithium battery separator with good temperature resistance, high ionic conductivity and excellent electrolyte affinity, which meets the application requirements of the separator in the field of lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery separators, and in particular relates to a lithium battery separator and a preparation method thereof. Background Art

[0002] The diaphragm is one of the key components in the battery. Currently, the commercial lithium battery diaphragms are mainly polyolefin microporous membranes, such as polyethylene (PE) and polypropylene (PP) diaphragms. Although this type of diaphragm has good electrochemical stability and mechanical strength, due to the inherent non-polar surface and low melting temperature of the material itself, polyolefin diaphragms have problems such as poor wettability to electrolytes and poor thermal stability, which affects the electrochemical performance and safety performance of the battery, which also restricts the development of high-performance lithium-ion batteries. Therefore, the preparation of high-performance battery diaphragms with high electrolyte absorption rate, high thermal stability and excellent electrochemical performance is of great significance to the development of lithium batteries.

[0003] Nanofiber coated diaphragm refers to coating nanoscale fibers on a base membrane to modify the surface of the existing diaphragm. On the one hand, it can improve the diaphragm's resistance to high-temperature shrinkage. On the other hand, it can improve the electrode compatibility and adhesion of the battery diaphragm, and increase the diaphragm's absorbency and affinity for the electrolyte.

[0004] At present, the main components of nanofiber coatings are cellulose nanofibers and polyvinylidene fluoride nanofibers. The surface-coated modified diaphragm greatly improves the high temperature resistance and safety of the battery, and can achieve effective electrolyte penetration and high wettability to aqueous electrolytes. However, exposure of cellulose fibers to aqueous solutions will lead to hydrogen bond rearrangement, coating expansion, and destruction of the ion transmission channels of the diaphragm. The temperature resistance of polyvinylidene fluoride nanofiber coatings also needs to be improved.

[0005] The Chinese patent with application number 202110431425.8 discloses a para-aramid nanofiber / inorganic nanoparticle composite coating reinforced polyolefin battery separator and preparation method. ANFs / Al2O3 and ANFs / SiO2 dispersions are prepared by combining aramid nanofibers with inorganic nano-aluminum oxide and silicon dioxide, and a thin film is added to the surface of the commercial polyolefin separator by coating or spin coating. The film-forming and mechanical properties of aramid nanofibers are fully utilized, the temperature resistance of the separator is improved, and the surface hydrophobicity of the separator is improved. However, dimethyl sulfoxide is used as the aramid nanofiber solvent in the preparation process of the separator, and inorganic nanoparticles are added to achieve uniform dispersion of organic and inorganic substances. Dimethyl sulfoxide is harmful to human health and difficult to recycle. Summary of the invention

[0006] The object of the present invention is to provide a lithium battery separator and a preparation method thereof, so as to solve the problems of poor temperature resistance and electrolyte wettability of the lithium battery separator.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] The present invention provides a lithium battery separator, which comprises a polyolefin separator substrate and a polymer nanofiber coating coated on the upper and lower surfaces thereof, wherein the main component of the polymer nanofiber coating is mixed nanofibers;

[0009] The hybrid nanofibers include three types of nanofibers: polyphenylene sulfide nanofibers, polylactic acid nanofibers and polyacrylonitrile nanofibers;

[0010] The mass proportions of the three types of nanofibers in the mixed nanofibers are: 50%≤polyphenylene sulfide nanofiber≤70%, 5%≤polylactic acid nanofiber≤20%, and the balance is polyacrylonitrile nanofiber. Too high a content of polylactic acid nanofiber will affect the temperature resistance of the diaphragm.

[0011] Further, the polyolefin diaphragm substrate includes one of a PP diaphragm, a PE diaphragm, a PP / PE / PP diaphragm and a PP / PE diaphragm;

[0012] The thickness of the polyolefin diaphragm substrate is 10-20 μm;

[0013] The polymer nanofiber coating has a thickness of 4-10 μm.

[0014] Furthermore, the nanofiber has a diameter of 10 nm-2000 nm and a length of 1 μm-10 μm.

[0015] The present invention also provides a method for preparing a lithium battery separator, which is used to prepare the lithium battery separator, comprising the following steps:

[0016] S1: adding polyphenylene sulfide nanofibers, polyacrylonitrile nanofibers and polylactic acid nanofibers into an ethanol aqueous solution and ball milling to obtain a nanofiber mixed solution;

[0017] S2: adding a dispersant and a surfactant to the above nanofiber mixed solution for ultrasonic dispersion to obtain a polymer nanofiber mixed dispersion;

[0018] S3: adding a defoamer and a binder to the above polymer nanofiber mixed dispersion and stirring, and mixing evenly to obtain a polymer nanofiber slurry;

[0019] S4: coating the polymer nanofiber slurry on the upper and lower surfaces of the polyolefin separator, and drying to form a coating to obtain the lithium battery separator.

[0020] Furthermore, the mass fraction of ethanol in the ethanol aqueous solution is 80%-90%, and the proportion of the mixed nanofibers to the ethanol aqueous solution is: 20g-50g of the mixed nanofibers are added to every 500mL of the ethanol aqueous solution.

[0021] Furthermore, the ball milling time is 8h-12h, and the ball milling speed is 200r / min-500r / min.

[0022] Furthermore, the dispersant includes at least one of polyethylene oxide and polyacrylamide, the surfactant includes at least one of sodium dodecyl sulfate, sodium stearate and Tween 80, the dispersant addition amount is 0.1%-0.5% of the mass of the nanofiber mixture, the surfactant addition amount is 0.05%-0.1% of the mass of the nanofiber mixture, the ultrasonic dispersion power is 500W-800W, the dispersion time is 30min-60min, and the dispersion temperature is room temperature.

[0023] Furthermore, the defoamer is a silicone defoamer, the binder is at least one of aqueous polyvinylidene fluoride, polyvinyl alcohol and carboxymethyl cellulose, the defoamer addition amount is 1%-10% of the mass of the polymer nanofiber mixed dispersion, the binder addition amount is 0.01%-2%, the stirring temperature is room temperature, and the stirring time is 4h-6h.

[0024] Furthermore, the polymer nanofiber slurry is coated by spin coating, roller coating or blade coating.

[0025] Furthermore, the drying temperature is 60°C-100°C, and the drying time is 12h-24h.

[0026] Beneficial effects of the present invention:

[0027] The coating is prepared by adopting the mixed dispersion method of polymer nanofibers to achieve mixed modification of polyphenylene sulfide, polyacrylonitrile and polylactic acid nanofibers. The heat resistance of polyphenylene sulfide fibers, the good electrochemical properties of polyacrylonitrile nanofibers and the hydrophilicity of polylactic acid nanofibers are combined. The properties of multiple polymer nanofibers are complementary, and the mixing can improve the overall performance of the diaphragm, thereby obtaining a lithium battery diaphragm with high temperature resistance, high wettability of aqueous electrolytes and high ionic conductivity. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] Polyphenylene sulfide nanofibers (diameter 1280nm, length 8μm), polyacrylonitrile nanofibers (diameter 500nm, length 5μm), and polylactic acid nanofibers (diameter 1000nm, length 7μm) were added to an ethanol aqueous solution (ethanol: water = 80:20) in a mass ratio of 11:7:2 and ball-milled. 50g of nanofibers were added to every 500mL of ethanol aqueous solution. The ball milling speed was set to 500r / min, and the ball milling was continued for 12h to obtain a nanofiber mixed solution.

[0031] 0.5% by weight of polyethylene oxide and 0.1% by weight of sodium dodecyl sulfate were added to the above nanofiber mixed solution for ultrasonic dispersion. The ultrasonic dispersion power was set to 800 W and the ultrasonic dispersion was continued for 30 minutes to obtain a polymer nanofiber mixed dispersion.

[0032] Add 3% by weight of polydimethylsiloxane and 1% by weight of aqueous polyvinylidene fluoride to the above polymer nanofiber mixed dispersion, stir, and continue stirring at room temperature for 6 hours to obtain a polymer nanofiber slurry after mixing evenly;

[0033] The polymer nanofiber slurry was scraped onto the upper and lower surfaces of a 15 μm thick PP diaphragm substrate, and dried at a constant temperature of 80°C for 12 hours to form a coating. The total thickness of the coating on the upper and lower surfaces was 10 μm, and a lithium battery diaphragm with a thickness of 25 μm was obtained.

[0034] Example 2

[0035] The other steps are the same as those in Example 1, and a PE diaphragm is used as the substrate. The substrate thickness and coating thickness are the same as those in Example 1.

[0036] Comparative Example 1

[0037] Commercial single-layer PP separator with a thickness of 25μm.

[0038] Comparative Example 2

[0039] Commercial single-layer PE separator with a thickness of 25μm.

[0040] The lithium battery separators of Example 1, Example 2 and Comparative Example 1, Comparative Example 2 were subjected to performance tests according to the standards for battery separator performance tests. The results are shown in Table 1.

[0041] The thermal shrinkage test method is: place the sample in a 130°C oven for heat treatment for 60 minutes, and then measure the change in the diaphragm area before and after the heat treatment.

[0042] Table 1

[0043] project Example 1 Example 2 Comparative Example 1 Comparative Example 2 Thermal shrinkage 2.8% 3.3% 12.0% 20.5% Ionic conductivity (S / cm) <![CDATA[2.0×10 -3 ]]> <![CDATA[2.2×10 -3 ]]> <![CDATA[0.3×10 -3 ]]> <![CDATA[0.5×10 -3 ]]> Electrolyte contact angle 32.8° 28.0° 129.8° 110.2°

[0044] It can be seen from Table 1 that by coating the polymer nanofiber coating on the surface of the polyolefin separator, the thermal shrinkage of the separator at the same temperature is reduced, the hydrophilic groups are increased on the surface so that it has good wettability with the electrolyte, and the ionic conductivity is also significantly improved. The obtained lithium battery separator has excellent temperature resistance, hydrophilicity and electrochemical properties and can be used in high-performance lithium batteries.

[0045] Example 3

[0046] The other steps are the same as Example 1, and the proportion of polylactic acid nanofibers in the nanofibers is adjusted. Polylactic acid fibers directly affect the electrolyte affinity and temperature resistance of the lithium battery separator. The lithium battery separator and electrolyte contact angle and temperature resistance test results obtained with different proportions are shown in Table 2.

[0047] The thermal shrinkage test method is: place the sample in a 130°C oven for heat treatment for 60 minutes, and then measure the change in the diaphragm area before and after the heat treatment.

[0048] Table 2

[0049] Polylactic acid nanofiber ratio Contact angle Thermal shrinkage 5% 48.1° 1.2% 15% 21.7° 3.8% 20% 19.0° 10.2%

[0050] It can be seen from Table 2 that with the increase in the proportion of polylactic acid nanofibers in the three nanofibers, the contact angle of the lithium battery separator is significantly reduced, and the affinity with the electrolyte is improved. However, due to the poor temperature resistance of the polylactic acid nanofibers themselves, the thermal shrinkage rate increases significantly with the increase in content, which is not conducive to the thermal stability of the separator. Comprehensive analysis shows that the temperature resistance and hydrophilicity of the separator are better when its proportion is 5%-15%.

[0051] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0052] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A lithium battery separator, characterized in that: The diaphragm comprises a polyolefin diaphragm substrate and a polymer nanofiber coating coated on the upper and lower surfaces thereof, wherein the polymer nanofiber coating comprises mixed nanofibers; the polyolefin diaphragm substrate has a thickness of 10-20 μm; the polymer nanofiber coating has a thickness of 4-10 μm; The hybrid nanofibers include three types of nanofibers: polyphenylene sulfide nanofibers, polylactic acid nanofibers and polyacrylonitrile nanofibers; The mass proportions of the three types of nanofibers in the mixed nanofibers are: 50%≤polyphenylene sulfide nanofiber≤70%, 5%≤polylactic acid nanofiber≤20%, and the balance is polyacrylonitrile nanofiber.

2. A lithium battery separator according to claim 1, characterized in that: The polyolefin diaphragm substrate includes one of a PP diaphragm, a PE diaphragm, a PP / PE / PP diaphragm and a PP / PE diaphragm.

3. A lithium battery separator according to claim 1, characterized in that: The nanofiber has a diameter of 10 nm to 2000 nm and a length of 1 μm to 10 μm.

4. A method for preparing a lithium battery separator according to any one of claims 1 to 3, characterized in that: The steps include: (1) adding polyphenylene sulfide nanofibers, polyacrylonitrile nanofibers and polylactic acid nanofibers into an ethanol aqueous solution and ball milling to obtain a nanofiber mixed solution; (2) adding a dispersant and a surfactant to the nanofiber mixed solution and performing ultrasonic dispersion to obtain a polymer nanofiber mixed dispersion solution; (3) adding a defoaming agent and a binder to the above polymer nanofiber mixed dispersion and stirring, and mixing evenly to obtain a polymer nanofiber slurry; (4) The polymer nanofiber slurry is applied to the upper and lower surfaces of the polyolefin separator, and dried to form a coating to obtain the lithium battery separator.

5. A method for preparing a lithium battery separator according to claim 4, characterized in that: The mass fraction of ethanol in the ethanol aqueous solution is 80%-90%, and the proportion of the mixed nanofibers to the ethanol aqueous solution is: 20g-50g of the mixed nanofibers are added to every 500mL of the ethanol aqueous solution.

6. The method for preparing a lithium battery separator according to claim 4, characterized in that: The ball milling time is 8h-12h, and the ball milling speed is 200r / min-500r / min.

7. A method for preparing a lithium battery separator according to claim 4, characterized in that: The dispersant includes at least one of polyethylene oxide and polyacrylamide; The surfactant includes at least one of sodium dodecyl sulfate, sodium stearate and Tween 80; The amount of dispersant added is 0.1%-0.5% of the mass of the nanofiber mixture; The amount of surfactant added is 0.05%-0.1% of the mass of the nanofiber mixture; The ultrasonic dispersion power is 500W-800W, the dispersion time is 30min-60min, and the dispersion temperature is room temperature.

8. The method for preparing a lithium battery separator according to claim 4, characterized in that: The defoamer is an organosilicon defoamer; The binder is at least one of water-based polyvinylidene fluoride, polyvinyl alcohol and carboxymethyl cellulose; The amount of defoamer added is 1%-10% of the mass of the polymer nanofiber mixed dispersion; The amount of binder added is 0.01%-2% of the mass of the polymer nanofiber mixed dispersion; The stirring temperature is room temperature and the stirring time is 4h-6h.

9. The method for preparing a lithium battery separator according to claim 4, characterized in that: The polymer nanofiber slurry is coated by spin coating, roller coating or blade coating.

10. The method for preparing a lithium battery separator according to claim 4, characterized in that: The drying temperature is 60° C.-100° C., and the drying time is 12 h-24 h.

Citation Information

Patent Citations

  • Para-aramid nanofiber / inorganic nanoparticle composite coating reinforced polyolefin battery diaphragm and preparation method thereof

    CN113206345A

  • Non-woven fabric and preparation method thereof, lithium battery diaphragm and lithium battery diaphragm base membrane

    CN114080723A

  • Cellulose fibre-based separators for electrochemical elements

    CN116325330A

  • Lithium ion battery diaphragm, preparation method thereof and lithium ion battery

    CN117977102A